Effects of tetrandrine on rabbit platelet aggregation, thromboxane A2 generation and calmodulin activity - Qian Yue-ming; Huang Yue-hua (Acta Pharmacologica Sinica, 2016)
The effects of tetrandrine (Tet) on platelet aggregation and thromboxane A2 (TXA2) generation were studied in rabbit platelet-rich plasma (PRP) prepared by centrifugation. The effects of Tet on calmodulin activity in platelet extracts were also investigated by measuring calmodulin-sensitive phosphodiesterase activity. ADP, collagen or arachidonic acid (AA)-induced platelet aggregation was inhibited by Tet in a dose-dependent manner. TXA2 generation in PRP treated by Tet was markedly decreased in collagen-induced group, but was not altered in AA-induced group, suggesting that the release of AA from platelet phospholipids stimulated by collagen was blocked by Tet. Further experiments showed that the effects of Tet were related to its inhibition of calmodulin-dependent phosphodiesterase activity. There was evidence that the effects originated from its anti-calmodulin properties instead of its direct action on phosphodiesterase.